A characteristic feature of biological membranes - Tog`ayeva, Muhayyo (Центр Научных Публикаций (buxdu.uz), 2023)
Studying the structure of biological membranes in the article we will look at the various components of the plasma membrane, their functions, diversity and how they make the cell changeable, receptive and work together to create a safe boundary around the cell